2023
DOI: 10.1186/s43163-023-00393-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autism spectrum disorder among children referred to special needs clinic in Giza

Abstract: Background Little is known about the prevalence of autism spectrum disorder (ASD) among the population with disability in Egypt. Furthermore, the increasing prevalence of ASD and the variability of the ASD manifestations and severity highlight the importance of investigating the ASD comorbidities. Aim of work This analysis was to compare the prevalence of autism with that of other disabilities among children visiting the clinic for special needs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…ASD affects around 1-1.5% of the global population, highlighting its significant impact [2]. A prevalence study conducted in Giza from 2019 to August 2022 showed that 3,355 children visited a special needs clinic, indicating the prevalence of ASD in that population [3].…”
Section: Introductionmentioning
confidence: 99%
“…ASD affects around 1-1.5% of the global population, highlighting its significant impact [2]. A prevalence study conducted in Giza from 2019 to August 2022 showed that 3,355 children visited a special needs clinic, indicating the prevalence of ASD in that population [3].…”
Section: Introductionmentioning
confidence: 99%